2018
DOI: 10.1007/s13197-018-3204-0
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical, antioxidant and sensory characteristics of sponge cakes fortified with Clitoria ternatea extract

Abstract: Bakery products are a food appreciated by consumers all over the world. There is a great opportunity to incorporate more bioactive compounds to enhance its quality. The objective of this study was to utilize the advantage of CTE in the production of sponge cake. The five different levels of CTE (0, 5, 10, 15 and 20%, w/w) was incorporated into sponge cake. The sponge cakes were evaluated for physicochemical (color, volume, water activity, total phenolic content, and antioxidant properties) and texture characte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
21
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(32 citation statements)
references
References 31 publications
3
21
0
1
Order By: Relevance
“…Specifically, the deep blue color of C. ternatea flowers is a particularly sought after alternative to synthetic blue food colorants which have become increasingly disfavored due to health concerns (Nigg et al, 2011). Studies reported that addition of C. ternatea extracts increased the polyphenolic and antioxidant contents of sponge cakes (Pasukamonset et al, 2018), enhanced the oxidative stability of cooked pork patties (Pasukamonset et al, 2017) and reduced the predicted glycemic index of flour (Chusak et al, 2018a). Microencapsulation using alginate prevented the degradation and enhanced the retainment of the antioxidant activities of C. ternatea polyphenolic extracts post gastrointestinal digestion (Pasukamonset et al, 2016).…”
Section: Next Generation Applicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Specifically, the deep blue color of C. ternatea flowers is a particularly sought after alternative to synthetic blue food colorants which have become increasingly disfavored due to health concerns (Nigg et al, 2011). Studies reported that addition of C. ternatea extracts increased the polyphenolic and antioxidant contents of sponge cakes (Pasukamonset et al, 2018), enhanced the oxidative stability of cooked pork patties (Pasukamonset et al, 2017) and reduced the predicted glycemic index of flour (Chusak et al, 2018a). Microencapsulation using alginate prevented the degradation and enhanced the retainment of the antioxidant activities of C. ternatea polyphenolic extracts post gastrointestinal digestion (Pasukamonset et al, 2016).…”
Section: Next Generation Applicationsmentioning
confidence: 99%
“…In 2003, comparison of C. ternatea lines bearing different floral colors provided insights into the role of acylation on C. ternatea floral color determination (Kazuma et al, 2003a). The abundance of these unique anthocyanins alongside other secondary metabolites in C. ternatea makes the plant an ideal source of natural additives that can enhance the appearance and nutritive values of consumer products (Pasukamonset et al, 2016, 2017, 2018; Siti Azima et al, 2017). Although a number of recent studies has endeavored to elucidate the pharmacological activities of C. ternatea (Adhikary et al, 2017; Kavitha, 2018; Singh et al, 2018), the contribution of individual extract components on any bioactivity measured remains unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Yogurt production with the addition of BPFE increase the antioxidant activity of all samples. Similar studies describe that the antioxidant activity can be improved by incorporating natural extracts into yogurt (Wallace & Giusti, 2008;Zhang et al, 2019;Anuyahonget al, 2020;Hussein, Awad, El-Sayed, & Ibrahim, 2020) and other food products, such as juices (Lakshan et al, 2019), cakes and bakery (Pasukamonset et al, 2018;Rashid et al, 2020). The addition of natural anthocyanin extract into yogurt has been the subject of many studies.…”
Section: Antioxidant Activitymentioning
confidence: 92%
“…At neutral pH, the color is blue, and the lower pH is purple. Anthocyanins in blue pea flowers have been used in beverage, bread, rice, and other products (Pasukamonset et al, 2018;Anuyahong et al, 2020;Rashid et al, 2020). It also can be used as an antimicrobial compound for food spoilage (Chusak, Thilavech, Henry, & Adisakwattana, 2018;Zingare, Zingare, Dubey, & Ansari, 2013;Dhanasekaran et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Consumption of bakery products, like cakes is increasing worldwide (Pasukamonset et al 2018). A serious and costly problem for bakery industry is the economic loss caused by microbial spoilage which is often the main factor limiting shelf life of intermediate and high moisture bakery goods (Smith et al 2004;Valle Garcia et al 2019).…”
Section: Introductionmentioning
confidence: 99%